A Rare Case of Triceps Brachii Injury after Electrocution - Lana, Debora; Tarallo, Luigi; Catani, Fabio (Journal of Hand and Microsurgery, 2018)
Injuries of the triceps brachii muscle are a rare entity and mostly concern its distal tendon. These represent the least common of all muscle and tendons injuries. The most common reported causes are repeated strong physical efforts, a fall on an outstretched forearm when a sudden deceleration is put on contract triceps, or a direct trauma. High-dosed and prolonged corticosteroid therapies, repeated local steroid injections, chronic renal failure, diabetes, rheumatoid arthritis, hyperparathyroidism, and osteogenesis imperfecta are reported as systemic causes. Even rarer are lesions of muscle fibers and avulsions or rupture at its musculotendinous junction, and these can be caused by direct trauma or by forced elbow flexion during triceps contraction. To the best of our knowledge, there is no article in the literature describing this type of injury that occurred after electrocution. In this article, we report an uncommon case of intramuscular tear associated with insertional distal tendon injury occurred in a man survived to high-voltage electric discharge.
Keywords: electrocution; muscle; injury; triceps brachii